STATE AND SOME DEVELOPMENT PROBLEMS OF RUSSIAN MANUFACTURING INDUSTRY - M. L. Lezina; T.A. Kostenkova (Модернизация, инновация, развитие, 2016)
Production of domestic machine-building industry suffers with poor quality, hence it does not stand competition with similar products. Falling-off is characteristic for production of all branches of the industry. The state must create such economic conditions that would stimulate transition of these branches to the innovative development way. One of the main factors that brake innovative development of the Russian economy production sphere under examination is unsatisfactorymotivation and payment of personnel engaged.